A 7-Year Single-Center Experience of Transfemoral TAVI: Evolution of Surgical Activity and Impact on Vascular Outcome. (July 2018) - Lareyre, Fabien; Raffort, Juliette; Dommerc, Carine; Habib, Yacoub; Bourlon, François; Mialhe, Claude
Transcatheter aortic valve implantation (TAVI) has become a well-established alternative to open surgery to treat aortic stenosis. We describe our 7-year TAVI experience using transfemoral access and identity changes in surgical activity and evaluate its impact on postoperative vascular outcomes. Consecutive patients (N = 340) who underwent TAVI with percutaneous transfemoral access were retrospectively included and divided into 4 quartiles according to the date of intervention. Vascular outcomes were classified according to the Valve Academic Research Consortium 2 classification. The number of patients who underwent transfemoral TAVI increased over time and their clinical characteristics evolved, with a lower Society of Thoracic Surgeons score and less comorbidities. The material used evolved and TAVI could be performed despite higher iliac calcification and tortuosity scores. With experience, the procedural time, the postoperative length of stay at hospital, and the 30-day postoperative mortality significantly decreased. No significant change was observed for vascular outcome, except for minor hematoma. We witnessed an increase in transfemoral TAVI procedure, with changes in clinical and procedural characteristics associated with an improvement in postoperative outcomes.